The relationship between mother’s knowledge and attitudes toward infant massage performed by traditional birth attendants - Rosmawaty Rosmawaty; Siti Hasriani; Wilda Rezki Pratiwi; Syahriani Syahriani; Satriani Satriani (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Baby massage is a traditional practice still often performed by traditional birth attendants (dukun) in various regions of Indonesia, including Amparita Village, Sidenreng Rappang District. Purpose: To determine the relationship between mothers’ knowledge and attitudes with the practice of baby massage performed by traditional attendants. Method: This research used a quantitative approach with a cross-sectional design. The sample consisted of mothers who have babies and live in Amparita Village. Data were collected using questionnaires and analyzed with the Chi-square statistical test. Results: The results showed a significant relationship between mothers’ knowledge and baby massage performed by traditional attendants (p<0.05). Mothers’ attitudes were also significantly associated with the decision to choose traditional attendants for baby massage (p<0.05). Conclusion: It is concluded that mothers’ knowledge and attitudes significantly influence the practice of baby massage by traditional attendants. Suggestion:  Educational interventions from health workers are needed to improve mothers’ understanding of the benefits and risks of baby massage and to encourage safe practices in accordance with health standards.